Written corrective feedback across different levels of EFL students’ academic writing proficiency: Outcomes and implications - Suhartawan Budianto; Teguh Sulistyo; Oktavia Widiastuti; Dwi Fita Heriyawati; Saiful Marhaban (Universitas Syiah Kuala, 2020)
This current research aimed at finding out the impact of different feedback modes, that is indirect corrective feedback and direct corrective feedback, on the writing proficiency of EFL students at the university level. Direct and indirect corrective feedbacks were provided by covering global and local aspects of writing together. This study reported on a 14-week study with 63 students majoring in the English Education Department of an outstanding university in Surabaya, Indonesia. The pre-test was given to 35 students that belonged to a high proficiency level group, whereas 28 students belonged to the low proficiency level. The proficiency level was used to examine whether the corrective feedback was effective for certain levels of learners’ proficiency. An experimental design was run to examine whether there was a noteworthy different impact of direct corrective feedback (DCF) and indirect corrective feedback (ICF) on descriptive essays produced by EFL students. Two groups of participants, DCF group and ICF group, wrote eight topics in which each was treated using different feedback. The results revealed that the DCF is more powerful than ICF and contributes significantly to improve students’ EFL writing, regardless of the students’ level of proficiency (high or low). The outcomes of DCF and ICF in the EFL writing process that do not depend on proficiency level indicates that the use of DCF and ICF is not influenced by proficiency level. In other words, direct corrective feedback is advantageous for both low and high proficiency learners in EFL writing process.